The Influence of Digital Technology on Human Resource Management Practice - Puspita S, Retno Ayu (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This article presents a systematic analysis of the influence of digital technologies on Human Resource Management (HRM) practices. Through the Systematic Literature Review method, we explore the impact of innovative digital technology on key aspects of HRM such as recruitment, employee development, performance management, and employee experience. The research results highlight significant changes in these practices, providing deep insight into the digital transformation occurring in the world of human resource management. The implications of these findings include increased efficiency, organizational adaptability to new working models, and emerging challenges around data security. This article provides valuable guidance for HRM practitioners and researchers to understand and respond to the evolution of HRM dynamics in the digital era.